Exploratory Study On The Students\' Perception Of Mobile Learning In A Malaysian Tertiary Institution - Hasyim, Hayati (2009)
This study examines the students\' perception of mobile learning in a university in Malaysia. Mobile learning is seen as a move forward from the e-learning systems but with an emphasis on the ubiquity where learning can be done anywhere, anytime. It has bring about increased convenience in learning environments and allows mobility of the users. The study aims to provide an indication of the learners\' perception on mobile learning, identify the most important and frequent mobile learning tool in their personal and portable mobile devices and explore the user group differences in their perception of their mobile learning concept.